2023
DOI: 10.3233/xst-221261
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-view X-ray digital imaging stitching algorithm

Abstract: BACKGROUND: In fan beam X-ray imaging applications, several X-ray images sometimes need to be stitched together into a panoramic image because of the size limitations of the detector. OBJECTIVE: This study aims to propose a novel multi-view X-ray digital imaging stitching algorithm (MVS) based on the CdZnTe photon counting linear array detectors to solve the problem of fan beam X-ray stitching deformation. METHODS: The panoramic image is generated in four steps including (1) multi-view projection data acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…And this also leads to a lack of deeper thinking and spirit in the current immersive 3D ink element animation, a lack of innovation, and the problem of repeated development [5]. The current solution to the problem of missing content is to transform the existing classic 3D ink element animation into immersive 3D ink element animation, which requires the use of image stitching algorithms [6]. At present, research on image stitching algorithms mainly focuses on the stitching of monocular images, with less involvement in the stitching of binocular images.…”
Section: Introductionmentioning
confidence: 99%
“…And this also leads to a lack of deeper thinking and spirit in the current immersive 3D ink element animation, a lack of innovation, and the problem of repeated development [5]. The current solution to the problem of missing content is to transform the existing classic 3D ink element animation into immersive 3D ink element animation, which requires the use of image stitching algorithms [6]. At present, research on image stitching algorithms mainly focuses on the stitching of monocular images, with less involvement in the stitching of binocular images.…”
Section: Introductionmentioning
confidence: 99%
“…Chai, X. C. et al used an up-scaling-down image sampling procedure to obtain pixel-level optimal stitching lines for large remote sensing images [13]. Kang, Y. et al proposed a novel multi-view X-ray digital imaging stitching algorithm (MVS) based on a CdZnTe photon-counting linear array detector to solve the problem of sector-beam X-ray stitching distortion [14]. From the existing research, most of the research is applied to industry, and there are few studies in agriculture, for example, few studies on the stitching technology of fruit tree branches and trunks have been reported.…”
Section: Introductionmentioning
confidence: 99%